Orthodontic extrusion for pre-implant site enhancement: Principles and clinical guidelines. Issue 3 (July 2016) - Alsahhaf, Abdulaziz; Att, Wael
Abstract: Purpose: The aim of this paper is to provide a concise overview about the principles of pre-implant orthodontic extrusion, describe methods and techniques available and provide the clinicians with guidelines about its application. Study selection: A number of reports describe orthodontic extrusion as a reliable method for pre-implant site enhancement. However, no standard protocols have been provided about the application of this technique. The literature database was searched for studies involving implant site enhancement by means of orthodontic extrusion. Information about the principles, indications and contraindications of this method, type of anchorage, force and time were obtained from the literature. Result: Despite that the scarce data is largely limited to case reports and case series, implant site enhancement by means of orthodontic extrusion seems to be a promising option to improve soft and hard tissue conditions prior to implant placement. Conclusion: Orthodontic extrusion is being implemented as a treatment alternative to enhance hard and soft tissue prior to implant placement. While the current literature does not provide clear guidelines, the decision making for a specific approach seems to be based on the clinician's preferences. Clinical studies are needed to verify the validity of this treatment option.